Pseudothinusa sunahama, a new genus and species of the tribe Athetini (Coleoptera, Staphylinidae, Aleocharinae) from sandy beaches in Japan - Tasaku, Yuto; Maruyama, Munetoshi (Zootaxa, 2023)
Pseudothinusa sunahama Tasaku & Maruyama gen. et sp. nov. (Aleocharinae) is described based on specimens collected from sandy beaches on the islands of Hokkaidô, Honshû, Shikoku, and Kyûshû, Japan. Pseudothinusa sunahama is the first Japanese athetine species discovered with spines on the front and middle tibiae.